Multiple narratives of il/legality and im/morality: The case of small-scale hashish harvesting in Kyrgyzstan - Botoeva, Gulzat (Theoretical criminology, 2021)
The aim of this study is to contribute to the current literature concerning the social acceptance of illegal practices. Using legal pluralism as a general framework of analysis, this study discusses the relationship between state law and alternative perspectives concerning its legitimacy. It presents the experience of people involved in hashish harvesting in one of the regions of Kyrgyzstan, how the state defines it as an ‘illegal practice’ and how the local population subsequently invokes normative systems based on local spiritual knowledge and the local moral economy of hashish production. It argues that acceptance of hashish harvesting as a legitimate means of support is not a straightforward process. Despite the predominant legitimating narrative of hashish harvesting, it enters into a conversation with state defined notions of ‘illegality’ and is also shaped by the customary understanding of the spiritual power of cannabis plants that requires caution when making hashish.